تاثير مستوى الهيموغلوبين المسكر وفرط الاكسدة في مرشى السكري - غالي, فراح (University of Thi-Qar Journal of Science, 2008)
This study was performed on (85) diabetic patients , classified as follows : 43 patients of type I (25 male and 18 femels) and 42 patients of type II (24 males and 18 femels .In addition , 55 healthy subjects were investigated as a control group. Both types showed a highly significant increase (P=0.0001) in blood glucose level ; 12.00 ± 3.96 mmole/l and 13.52 ±3.96 mmole/ l . for type I and II respectively compared to healthy subjects 4.63± 0.66 mmmole/l . This study also included the estimation of different biochemical parameters (Glycated hemoglobin HbA1c and malondialdehyde (MDA) in diabetic patients, in which both types showed a highly significant increase (P=0.0001) in blood HbA1 level 7.16 ± 0.62 μmole/l and 8.66 ± 0.50 μmole/l for type I and II respectively compared to healthy subjects 3.83 ± 0.40 μmole/l and in MDA level ; 12.22 ± 3.96 nmole/l and 13.52 ± 3.96 nmole/l for type I and II respectively compared to healthy subjects ; 14.63 ± 0.66 mole/l . The results of this study revealed a positive correlation of blood glucose level with glycated hemoglobin HbA; c for diabetic patients –type I( Correlation Coefficient =0.397) and type II (Correlation Coefficient =0.388 ) . Blood glucose level had a positive correlation also with malondialdehyde ( MDA) with correlation Coefficient =0.609 and 0.627 for type I and type II respectively .